Multiplex targeted high‐throughput sequencing in a series of 352 patients with congenital limb malformations. Issue 1 (23rd September 2019) - Jourdain, Anne‐Sophie; Petit, Florence; Odou, Marie‐Françoise; Balduyck, Malika; Brunelle, Perrine; Dufour, William; Boussion, Simon; Brischoux‐Boucher, Elise; Colson, Cindy; Dieux, Anne; Gérard, Marion; Ghoumid, Jamal; et al.
Abstract: Congenital limb malformations (CLM) comprise many conditions affecting limbs and more than 150 associated genes have been reported. Due to this large heterogeneity, a high proportion of patients remains without a molecular diagnosis. In the last two decades, advances in high throughput sequencing have allowed new methodological strategies in clinical practice. Herein, we report the screening of 52 genes/regulatory sequences by multiplex high‐throughput targeted sequencing, in a series of 352 patients affected with various CLM, over a 3‐year period of time. Patients underwent a clinical triage by expert geneticists in CLM. A definitive diagnosis was achieved in 35.2% of patients, the yield varying considerably, depending on the phenotype. We identified 112 single nucleotide variants and 26 copy‐number variations, of which 52 are novel pathogenic or likely pathogenic variants. In 6% of patients, variants of uncertain significance have been found in good candidate genes. We showed that multiplex targeted high‐throughput sequencing works as an efficient and cost‐effective tool in clinical practice for molecular diagnosis of congenital limb malformations. Careful clinical evaluation of patients may maximize the yield of CLM panel testing.